CRAWDAD a community resource for archiving wireless data at Dartmouth. - Yeo, Jihwang
Wireless network researchers are seriously starved for data about how real users, applications, and devices use real networks under real network conditions. CRAWDAD, a Community Resource for Archiving Wireless Data at Dartmouth, is a new NSF-funded project to build a wireless network data archive for the research community. We host wireless data, and provide tools and documents to make it easy to collect and use wireless network data. We hope that this resource will help researchers identify and evaluate real and interesting problems in mobile and pervasive computing. This report outlines the CRAWDAD project, the kick-off work-shop that was held at MobiCom 2005, and the latest news. how real users, applications, and devices use real networks under real conditions, and how mobile users actually move about. This data helps us to identify and understand the real problems, to evaluate possible solutions, and to evaluate new applications and services.
Keywords: Information systems; Information systems applications; Measurement